Predictability of 6 Intraocular Lens Power Calculation Formulas in People With Very High Myopia - Chu, Yi-Ching; Huang, Tzu-Lun; Chang, Pei-Yao; Ho, Wei-Ting; Hsu, Yung-Ray; Chang, Shu-Wen; Wang, Jia-Kang (Frontiers in Medicine, 2022)
Purpose To investigate the accuracy of 6 intraocular lens (IOL) power calculation formulas in predicting refractive outcome in extremely long eyes. Setting Department of Ophthalmology, Far Eastern Memorial Hospital, Taiwan Design Retrospective comparative study Methods In this retrospective single-center study, we reviewed 70 eyes of 70 patients with axial length (AL) ≥ 28 mm who received uneventful 2.2-mm corneal wound phacoemulsification and IOL in-the-bag placement. The actual postoperative refractive results were compared to the predicted refraction calculated with 6 formulas (Haigis, Hoffer Q, Holladay 1, SRK/T, T2, Barrett Universal II formulas) using IOLMaster 500 as optical biometry in User Group for Laser Interference Biometry (ULIB) constants. Results Over all, the Haigis and Barrett formulas achieved the lowest level of mean prediction error (PE) and median absolute error (MedAE). The Hoffer Q, Holladay 1, SRK/T, and T2 produced hyperopic prediction errors (p < 0.05). The Hoffer Q and Holladay 1 had significantly more MedAE between 6 formulas. After the mean PE have been zeroed out, the MedAE had no significant difference between each group. The absolute error tends to be larger in longer AL. The absolute errors were 30.0-37.1% and 60.0-64.3% within 1.0 D of all patients compared to predicted refraction calculated in various formulas. Conclusion In conclusion, the Haigis and Barrett universal II formulas had a better trend of in predicting IOL power in high myopic eyes with AL longer than 28 mm using ULIB constant in this study. The postoperative refractive results were inferior to the benchmark standards, which indicated the precision of IOL power calculation in high myopes still required improvement.